Important Letters on Various Matters Concerning Irrigation and Power Issued From the Planning Commission To the State Governments, Etc. - Planning Commission (Planning Commission, 1954)
While the general scheme of detailed working estimates, rates and other design features manner of construction etc. should be all approved by the Chief Engineer in charge of the project or other person to whom those duties arc delegated, the technical sanction after such general approval should be delegated in a liberal measure to the Executive Engineer in charge of the dam. The ordinary money limits should be increased, doubled or oven trebled in the matter of technical sanctions to detailed working estimates. Similarly in the matter of job work agreements and essential purchases of stores and machinery stores liberal powers should be delegated to Executive Engineers subject always to general and overall control of the Chief Engineer.
Government of India Planning Commission
Government of India Planning Commission